2005
DOI: 10.1007/s10120-005-0329-4
|View full text |Cite
|
Sign up to set email alerts
|

VEGF significance in peritoneal recurrence from gastric cancer

Abstract: VEGF score was a significant parameter of peritoneal recurrence. Conclusion. These results suggested that VEGF was correlated with peritoneal metastasis from gastric cancer, and that VEGF was a useful indicator of peritoneal recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
1
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 18 publications
(17 reference statements)
0
35
1
1
Order By: Relevance
“…Studies on the role of the VEGF family in gastric cancer have focused on individual VEGF members and their respective receptors [14,15,18] . The evaluation of the simultaneous expression of VEGF family members and their receptors may provide more accurate prognostic information [17] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Studies on the role of the VEGF family in gastric cancer have focused on individual VEGF members and their respective receptors [14,15,18] . The evaluation of the simultaneous expression of VEGF family members and their receptors may provide more accurate prognostic information [17] .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that high serum VEGF levels correlate with poor prognosis in certain hematological malignancies [28,29] . In gastric cancer, it has been shown that serum VEGF-A levels correlated with local tumor extent, disease stage, and the presence of distant metastases, and is an independent prognostic factor for patient survival [14,15,20] . Recently, Wang et al [9] reported that serum VEGF-C levels might be a useful biomarker to determine the presence of lymph node metastasis in patients with gastric cancer as well as correlate with VEGF-C tissue expression [18] .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Angiogenic factors such as vascular endothelial growth factor (VEGF)-A and VEGF-C secreted from peritoneal free cancer cells induce vascular neogenesis in the peritoneal-blood barrier. (24,25) As a result, the distance of the peritoneal-blood barrier shortens and an environment with a rich vasculature is established. VEGF is a well-known angiogenic factor that induces a mitogenic signal for endothelial cells by binding to endothelial cell receptors VEGFR-1 (Flt-1) and VEGFR-2 (KDR).…”
Section: Molecular Mechanisms Of Peritoneal Disseminationmentioning
confidence: 99%